IMPLEMENTASI PENGAMANAN OBJEK VITAL OLEH KEPOLISIAN DAERAH SULAWESI UTARA DI KOTA MANADO - Vicky ., Tandaju; Novie R. Pioh; Alfon ., Kimbal (Sam Ratulangi University, 2021)
This research aims to analyze the implementation of the security of vital objects by the Directorate of Security of Vital objects of the North Sulawesi Region Police in Manado City. This research was carried out at the Directorate of Security of Vital Objects of the Regional Police of North Sulawesi Province and several vital objects in Manado City. This research used qualitative research methods to explore in depth the problems that occur. The instruments used were direct observation in the field, literature and in-depth interviews with 15 informants. From the results of research in the field, it was found that the security of vital objects from the organizational aspect is still experiencing obstacles where the unit tasked with securing vital objects in Manado City is not yet clear, from the aspect of interpretation or understanding there are still obstacles to the understanding of vital object managers who do not consider security. as an investment then from the application aspect there are still some members who are negligent in carrying out their duties. Therefore the importance of socialization to managers of vital objects and also coordination between units in securing vital objects so that the implementation of policies for securing vital objects in Â Â Manado City goes well.